The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.nlm.2012.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Stress during puberty boosts metabolic activation associated with fear-extinction learning in hippocampus, basal amygdala and cingulate cortex

Abstract: a b s t r a c tAdolescence is characterized by major developmental changes that may render the individual vulnerable to stress and the development of psychopathologies in a sex-specific manner. Earlier we reported lower anxiety-like behavior and higher risk-taking and novelty seeking in rats previously exposed to peripubertal stress. Here we studied whether peri-pubertal stress affected the acquisition and extinction of fear memories and/or the associated functional engagement of various brain regions, as asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 55 publications
0
19
0
3
Order By: Relevance
“…Recently, a study in rhesus monkeys has shown that single nucleotide polymorphisms in the Crhr1 gene affect both anxiety temperament and metabolic activity in the anterior hippocampus and amygdala (Rogers et al, 2013). Interestingly, our previous data have also highlighted changes in the metabolic activity of hippocampus and amygdala in peripubertally stressed rats (Toledo-Rodriguez et al, 2012;Marquez et al, 2013). Furthermore, increasing CRH drive occurring specifically in the central amygdala through lentiviral-induced neuropeptide overexpression was also found to enhance anxiety-like (Flandreau et al, 2012) and depression-like (Keen-Rhinehart et al, 2009) behaviors in rats.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Recently, a study in rhesus monkeys has shown that single nucleotide polymorphisms in the Crhr1 gene affect both anxiety temperament and metabolic activity in the anterior hippocampus and amygdala (Rogers et al, 2013). Interestingly, our previous data have also highlighted changes in the metabolic activity of hippocampus and amygdala in peripubertally stressed rats (Toledo-Rodriguez et al, 2012;Marquez et al, 2013). Furthermore, increasing CRH drive occurring specifically in the central amygdala through lentiviral-induced neuropeptide overexpression was also found to enhance anxiety-like (Flandreau et al, 2012) and depression-like (Keen-Rhinehart et al, 2009) behaviors in rats.…”
Section: Discussionmentioning
confidence: 71%
“…The peripubertal period is a biological transitional phase involving adaptations in hormonal systems and neural circuits, including those related to stress and the development of emotionality (Spear, 2009;Romeo, 2010). In our lab, exposure of rats to stressful experiences (e.g., synthetic fox odor and exposure to an elevated platform) on scattered days during the peripuberty period (P28eP30, P34, P36, P40 and P42) was found to induce long-lasting effects on anxiety and stress-coping behaviors, including deficits in social behaviors (Toledo-Rodriguez and Sandi, 2011;Cordero et al, 2012;Marquez et al, 2013), as well as changes in metabolic responses in limbic brain regions including the hippocampus and the amygdala (Toledo-Rodriguez et al, 2012;Marquez et al, 2013). Here, we sought to investigate whether peripuberty stress would lead to alterations in the CRH system in limbic areas and whether pharmacological treatment with a CRHR1 antagonist during the immediate post-stress developmental period (i.e., adolescence) would reverse the long-term behavioral consequences of peripuberty stress.…”
Section: Introductionmentioning
confidence: 94%
“…An important extension to this approach has been to measure patterns of endogenous activation, simultaneously in multiple brain regions, associated with population and/or strain differences in extinction. Neuronal correlates of individual differences in extinction have been examined using imaging techniques, including metabolic mapping (via 2-deoxyglucose uptake [27]) and, in particular, quantification of immediate-early gene (IEG) expression, which is a marker of neuronal activation (reviewed in [28]). These studies reveal how impaired extinction is associated with patterns of aberrant neuronal activation in relevant brain circuits.…”
Section: Cortico-amygdala Circuitry Associated With Variation In Extimentioning
confidence: 99%
“…* p < 0,02 по вiдношенню до групи 3-мiсячних кастрованих тварин; ** p < 0,02 по вiдношенню до групи 3-мiсячних кастрованих та стресованих тварин; 1) p < 0,03 по вiдношенню до групи 2-мiсячних тварин контрольної групи; 2) p < 0,01 по вiдношенню до групи 3-мiсячних тварин контрольної групи; 3) p < 0,03 по вiдношенню до групи 2-мiсячних кастрованих тварин; 4) p < 0,03 по вiдношенню до групи 2-мiсячних кастрованих та стресованих тварин.…”
Section: т а б л и ц яunclassified
“…Процеси статевого розвитку ор-ганiзму генетично детермiнованi, але водно-час вони знаходяться пiд впливом ендоген-них та несприятливих факторiв середовища. Зокрема, численнi дослiдження останнiх де-сятилiть дають можливiсть стверджувати, що в перiодi статевого дозрiвання змiню-ється стiйкiсть органiзму до стресу [1][2][3]. Са-ме це може служити однiєю з причин значно-го поширення в пубертатному вiцi серцево-судинних захворювань, неврозiв, патологiї шлунково-кишкового тракту [4,5].…”
unclassified